Comparative genome based cis-elements analysis in the 5′ upstream and 3′ downstream region of cell wall invertase and Phenylalanine ammonia lyase in Nicotiana benthamiana. (February 2018) - Sheshadri, S.A.; Nishanth, M.J.; Harita, N.; Brindha, P.; Bindu, S.
Graphical abstract: Highlights: Cis -elements of CWIN and PAL may co-regulate primary and secondary metabolisms in Nicotiana benthamiana . Stress-responsive cis -elements of CWIN are: AHBP, L1BX, MYBL, MADS, MYBS, GTBX, DOFF and CCAF (5'); AHBP, MYBL, L1BX, HEAT, CCAF and KAN1 (3'). 5' region of NbCWINs showed evolutionary similarity to phenylpropanoid metabolism gene 4CL and redox gene SOD . The 3' region of NbCWINs were more related to other plant CWINs, followed by SOD and primary metabolism gene Aldolase . Our in-silico cis- element analysis can provide a basis to modulate diverse metabolisms under adverse conditions in planta . Abstract: Plant secondary metabolites are widely used in human disease treatment; though primary metabolism provides precursors for secondary metabolism, not much has been studied to unravel the link connecting both the processes. Most common form of gene regulation interconnecting diverse metabolism occurs at the transcriptional and/or posttranscriptional level mediated by regulatory cis -elements. The present study aims at understanding the common cis -elements network connecting the major primary metabolic enzyme, cell wall invertase ( CWIN ) and secondary metabolism genes in Nicotiana benthamiana ( N. benthamiana ). The CWIN and thirty one other gene sequences were extracted from N. benthamiana genome, followed by cis -element analysis of their 5′ upstream and 3′ downstream region using different programs (Genomatix software suite; PLACE and PlantCARe). Comparative cis -element analysis of CWIN ( N. benthamiana and other plant species) and other primary, secondary metabolism and transcription factor genes ( N. benthamiana ) revealed the occurrence of common stress associated cis -elements. Predominantly, AHBP, L1BX, MYBL, MADS, MYBS, GTBX, DOFF and CCAF were found in the 5′ upstream region of all genes, whereas AHBP, MYBL, L1BX, HEAT, CCAF and KAN1 were largely occurring in the 3′ downstream region of all genes; indicating common function of these elements in transcriptional and posttranscriptional gene regulation. Further, genomic analysis using FGENESH, GenScan and homology based methods (BlastX and BlastN) was performed on the N. benthamiana contigs harboring CWIN and PAL, in an attempt to identify genomic neighborhood genes. The 5′ upstream and 3′ downstream region of genes in the genomic neighborhood of CWIN and PAL were also subjected to similar cis -element analysis, and the results indicated cis- elements profile similar to CWIN, PAL and other primary, secondary metabolism and transcription factor genes. The results of evolutionary studies confirmed that the 5′ upstream region of NbCWINs significantly showed more proximity to secondary metabolism genes 4CL and the redox gene SOD, followed by the phenylpropanoid pathway gene CHI. The 3′ downstream regions of NbCWINs were more closely related to other plant CWINs, followed by the redox gene, SOD and primary metabolism gene FBA . Thus, the commonly found stress responsive cis- elements in our study can play a vital role in modulating key pathways of both primary and secondary metabolism; thereby postulating their role in regulating plant growth and metabolisms under unfavourable growth conditions.